Investigation of pedestrian crossing facilities along Jalan Ampang - Naser, Mohamed M Muftah (2017)
Most individual journey no matter what the basic user mode, starts or ends with walking section; so, walking is an essential element of all travel. Walking Behavior the pedestrian flow characteristics lay the foundation for planning and design walking facilities. Therefore, needs must be access to pedestrian facilities in the design of transport facilities. Includes pedestrian facilities Sidewalks, tracks, corridors, and stairs, reduction of cuts and ladders, and transit positions. These facilities should be carefully assessed for mitigation Congestion and enhanced walking in the central business area and sustainable society. But traditional valuation methods are flawed, new the approach to improving the current assessment must be constantly investigated Methods. The study assesses corridors and passages in the city Kuala Lumpur, Jalan Ampang. The results for traffic volume flow with the pedestrian crossing account at signalized and illegal indicated that the number for all vehicles, motorcycle, adult male, adult female, pedestrian signalized crossing and pedestrian illegal crossing varies considerably depending on the time range (30 minutes). The total number of 4-wheel vehicles were more than the total number of motorcycles. Also, the total number of pedestrians on the signalized and crossing in relation to the pedestrians crossing street, pedestrian crossing behavior (walked/origin time or waiting/crossing time to walked/destination time) were recorded and analyzed video graphic survey methods was used for pedestrian counts, having advantage over the manual method. Flow, speed, density and effective width of the walkway were the variables measured. Some on the positions identified, or office after extracting the data from the video. Hand tape, masking tape, stop watch and video camera/ tripod stand were the tools/apparatus used on various positions for collecting data. The flow rate calculated, in conjunct ion with HCM were used to estimate LOS. Analysis was conducted on the flaws identified so as to improve on the current method of estimation.